Window function for chirped pulse spectroscopy with enhanced signal-to-noise ratio and lineshape correction. (July 2021) - Zou, Luyao; Motiyenko, Roman A.
Highlights: Tunable asymmetric window function for chirped pulse spectroscopy. Lineshape correction to pure real Voigt profile. Signal-to-noise ratio enhancement. Abstract: In chirped pulse experiments, magnitude Fourier transform is used to generate frequency domain spectra. The application of window function as a tool for lineshape correction and signal-to-noise ratio (SnR) enhancement is rarely discussed in chirped spectroscopy, with the only exception of using Kaiser-Bessel window and trivial rectangular window. We present a specific window function, called "Voigt-1D" window, designed for chirped pulse spectroscopy. The window function corrects the magnitude Fourier-transform spectra to Voigt lineshape, and offers wide tunability to control the SnR and lineshape of the final spectral lines. We derived the mathematical properties of the window function, and evaluated the performance of the window function in comparison to the Kaiser-Bessel window on experimental and simulated data sets. Our result shows that, compared with un-windowed spectra, the Voigt-1D window is able to produce 100% SnR enhancement on average.